Right atrium thrombus in the presence of an atrial septal defect: a case report - S. A. Chepurnenko; G. V. Shavkuta; A. A. Demidova (Кардиоваскулярная терапия и профилактика, 2023)
Introduction. Right atrial (RA) masses have a very different origin. They may be clots. Most often, thrombi from the inferior vena cava migrate to RA. At the same time, an isolated thrombus in RA is a rare finding.Brief description. The article presents a case of detection of a round mass in RA in combination with an atrial septal defect. The mass was discovered by chance during a cardiac ultrasound in a 71-year-old female patient who applied due to hypertension. Accurate determination of the mass structure was possible only after its removal and histological analysis. It turned out to be an organized thrombus with cystic degeneration.Discussion. When a volumetric formation in the RA cavity is detected, a differential diagnosis of a thrombus with primary benign (myxoma or fibroelastoma) and malignant (sarcoma, lymphoma) tumors, metastases, which are found much more often than with primary cardiac tumors. The case is of interest due to thrombus location in RA region without inferior vena cava thrombosis, in combination with an atrial septal defect. This could contribute not only to pulmonary artery embolism, but also cause a paradoxical embolism in systemic circulation vessels.